Randomised controlled trial of site specific advice on school travel patterns. Issue 1 (1st January 2003) - Rowland, D; DiGuiseppi, C; Gross, M; Afolabi, E; Roberts, I
Abstract : Aims: To evaluate the effect of site specific advice from a school travel coordinator on school travel patterns. Methods: Cluster randomised controlled trial of children attending 21 primary schools in the London boroughs of Camden and Islington. A post-intervention survey measured the proportion of children walking, cycling, or using public transport for travel to school, and the proportion of parents/carers very or quite worried about traffic and abduction. The proportion of schools that developed and implemented travel plans was assessed. Results: One year post-intervention, nine of 11 intervention schools and none of 10 control schools had travel plans. Proportions of children walking, cycling, or using public transport on the school journey were similar in intervention and control schools. The proportion of parents who were very or quite worried about traffic danger was similar in the intervention (85%) and control groups (87%). However, after adjusting for baseline and other potential confounding factors we could not exclude the possibility of a modest reduction in parental concern about traffic danger as a result of the intervention. Conclusions: Having a school travel coordinator increased the production of school travel plans but there was no evidence that this changed travel patterns or reduced parental fears. Given the uncertainty about effectiveness, the policy of providing school travel coordinators should only be implemented within the context of a randomised controlled trial.